2017
DOI: 10.30596/jasc.v1i1.1542
|View full text |Cite
|
Sign up to set email alerts
|

Production Development and Maize Consumption in North Sumatra Province

Abstract: The state of Indonesia is an agrarian country, most of its livelihoods are farming. In Indonesia, corn is one of the food ingredients that the government recommends because it sees the huge need of rice. The government made efforts to realize the self-sufficiency of corn production in North Sumatra Province. For that Prediction of corn production development is needed to know the expected target is achieved. Corn production prediction is done using linear trend line formula and data taken in the form

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Suggesting that, empowering the implementers to select approaches may have fostered a stronger sense of ownership and desire to work harder and achieve more. This notion is supported by previous research where social motivation was found to enhance community participation in community level development activities (Siregar & Sismudjito, 2016). The discretion also may have allowed Strategy 3 teams to be more flexible in their schedules around personal and local events.…”
Section: Discussionsupporting
confidence: 62%
“…Suggesting that, empowering the implementers to select approaches may have fostered a stronger sense of ownership and desire to work harder and achieve more. This notion is supported by previous research where social motivation was found to enhance community participation in community level development activities (Siregar & Sismudjito, 2016). The discretion also may have allowed Strategy 3 teams to be more flexible in their schedules around personal and local events.…”
Section: Discussionsupporting
confidence: 62%
“…With these various supporting factors, the development of the modern culinary industry in North Sumatra has bright prospects. It positively contributes to regional economic growth and the preservation of traditional culinary riches (Siregar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Indonesian people are consumers of corn which is the second staple food after rice. The market demand for corn continues to increase every year, along with the development of the livestock industry, especially chicken farming where 60% of the corn needs are used for animal feed [4] Total raw materials needed for the manufacture of poultry feed, the portion of corn is around 50% [5]. One of the efforts to increase corn productivity is to develop superior varieties that have high yields and are adaptive to certain environmental conditions.…”
Section: Introductionmentioning
confidence: 99%